Three WHEAT/CIMMYT elite lines released by Indian Council of Agricultural Research (ICAR) as varieties for North West India's smallholder farmers in record time - CGIAR Research Program on Wheat (2020)
Phenotyping data for grain yield, heat tolerance, resistance to yellow rust and spot blotch, to support ICAR-IIWBR (Indian Council of Agricultural Research-Indian Institute of Wheat and Barley Research), the national partner, led to multi-trait improvements (pest and disease resistance, early and terminal heat) that ICAR-IWWBR could turn into varieties released and available to farmers in record time.